THE FUTURE OF INTER-RELIGIOUS DIALOGUE THREATS AND PROMISES - S J Samartha (Journal of Dharma, 1994)
ment of Religions in Chicago. 1893, many events have taken place whose consequences affect human life even to this day. The two world wars, the first use of the atom bomb. the holocaust. the increasing power of technological culture on human life and the many smaller conflicts in various countries in which religions were involved in one way or another. have raised critical questions about the role of religions in history. The recent collapse of Marxism in Eastern Europe and the rise of religious Fundamentalism in many parts of the world also raise questions to which religious people do not have easy answers. It is in this context that the future of inter-religious dialogue has to be discussed. particualrly because there is a discernible ferment now at the inter-section where people of different religious commitments live and work together in society.